Usability of End-to-End Encryption in E-Mail Communication - Reuter, Adrian; Abdelmaksoud, Ahmed; Boudaoud, Karima; Winckler, Marco (Frontiers in Big Data, 2021)
This paper presents the results of a usability study focused on three end-to-end encryption technologies for securing e-mail traffic, namely PGP, S/MIME, and Pretty Easy Privacy (pEp). The findings of this study show that, despite of existing technology, users seldom apply them for securing e-mail communication. Moreover, this study helps to explain why users hesitate to employ encryption technology in their e-mail communication. For this usability study, we have combined two methods: 1) an online survey, 2) and user testing with 12 participants who were enrolled in tasks requiring e-mail encryption. We found that more than 60% of our study participants (in both methods) are unaware of the existence of encryption technologies and thus never tried to use one. We observed that above all, users 1) are overwhelmed with the management of public keys and 2) struggle with the setup of encryption technology in their e-mail software. Nonetheless, 66% of the participants consider secure e-mail communication as important or very important. Particularly, we found an even stronger concern about identity theft among e-mail users, as 78% of the participants want to make sure that no other person is able to write e-mail on their behalf.